Oral impacts of number of natural teeth and posterior occluding pairs on daily performance of geriatric population of Bareilly city: A cross-sectional study - Nandita Gautam; Anushtha Kushwaha; Suyash Singh; Siddhant Singh; Sonal Singh (Journal of Dental Problems and Solutions - Peertechz Publications, 2022)
Background: Poor oral health among the elderly has been measured in terms of tooth loss, dental caries, high prevalence rates of periodontal disease, xerostomia, and oral precancer/cancer around the world.  Aim: The study's goal is to see how posterior occluding pairs and the total number of natural teeth in the mouth affect everyday activity in the elderly.  Materials and methods: It was cross-sectional research with 300 participants drawn from a physiotherapy hospital by convenience sampling. The participants were asked about their age, gender, cigarette usage, oral hygiene practices, regularity of use, type of materials utilized, quality of life dental health and other xerostomia symptoms. The oral influences on the daily performance index were used to measure the effects on daily performance. The number of NT and POPs was counted during a clinical evaluation.  Results: The studied population's general average age was 63.81 4.50, with no statistically significant differences between men and women. Overall, the research sample had a mean number of NT of 24.76 7.21, with men having 25.90 6.29 and women having 23.32 8.03. Conclusion: The number of NT and POPs was discovered to be important determinants of daily performance among the geriatric population.